A CFD- RSM study of cuttings transport in non-Newtonian drilling fluids: Impact of operational parameters - Abdelrahman M. Awad (16932519) (2022)
Cuttings removal out of the wellbore represents a real barrier for successful drilling operations. The performance of hole cleaning is determined by several factors. The current article provides a theoretical study of the impact of three operational parameters on cuttings transport in non-Newtonian drilling fluids. Computational fluid dynamics (CFD) is used to study the effect of drill pipe rotation speed (from 0 to 200 rpm), inclination angle (0–90⁰), and pipe eccentricity (0–0.8) on the cuttings transport ratio (CTR), cuttings volume concentration (CVT), and pressure drop. Response surface methodology (RSM) is employed to explore the two-factor interactions and to optimize the parameters by minimizing the CVT while maximizing the CTR. RSM is also used to generate statistical models to correlate the impact of the aforementioned three factors to the hole cleaning performance (represented by CVT, CTR, and pressure drop). Results revealed that many interactions exist between the tested operational parameters. The drill pipe rotation has the dominant effect on the performance of cuttings transportation, with the effect are more pronounced for highly deviated and horizontal wells. The results indicate that there are only a few cases of inadequate hole cleaning that drill-pipe rotation cannot control, and those cases are associated with the operation in vertical wellbore sections. Less effective cuttings transportation (i.e lower CTR) was observed when the hole angle deviated from the vertical. In addition, a significantly higher CVT (up to 73%) was recorded for eccentric pipes as compared to the concentric cases, primarily due to the reduced fluid velocity in the narrow gap of the eccentric annulus. As far as the pressure drop is concerned, lower pressure loss was obtained at lower rotation speeds and higher angles of inclination from the vertical. As the drill pipe rotational speed increased, the pressure drop decreased slightly until a critical rotatory speed was reached, thereafter, the pressure drop increased markedly. This trend was similar for all pipe eccentricities at any inclination angles, however, the critical rotational speed at which the pressure loss started to increase was found to be dependent on both the inclination angle and eccentricity. Operating at low drill pipe rotation speeds in a concentric annulus is recommended for vertical wells while higher speeds are favorable for more effective cuttings transport in horizontal wells. The CFD simulation results have been validated against experimental measurements for single and multiphase flow for different cases with/without drill pipe rotation at various inclination angles for both Newtonian and Non-Newtonian fluids. Other Information Published in: Journal of Petroleum Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.petrol.2021.109613